Pluchea lanceolata protects against Benzo(a) pyrene induced renal toxicity and loss of DNA integrity - Jahangir, Tamanna (Slovak Toxicology Society SETOX, 2013)
Evidence from epidemiological, experimental and clinical trial data indicates that a plant based diet can reduce the risk of chronic diseases and reduces toxic effects. In the present study, we report the antioxidant and anticlastogenic activity of Pluchea lanceolata (PL), an important medicinal plant, in both in vitro and in vivo model. Benzo(a)pyrene (B(a)P) administration leads to depletion of renal glutathione and its metabolizing enzymes. Pretreatment with PL (100 and 200 mg /kg b.wt) restored renal glutathione content and its dependent enzymes significantly (p<0.001) with simultaneous increase in catalase(CAT), quinone reductase(QR) in mouse kidney. Prophylactic administration of PL prior to B (a) P administration significantly decreased the malondialdehyde(MDA), H(2)O(2) and xanthineoxidase (XO) levels at a significance of p<0.001, at both the doses. PL extract pretreated groups showed marked inhibition in B(a)P induced micronuclei formation in mouse bone marrow cells with simultaneous restoration of DNA integrity, viz. alkaline unwinding assay and DNA damage shown by gel-electrophoresis. HPTLC confirms the presence of quercetin in plant extract which could be responsible for PL protecting efficacy. In conclusion, the present findings strongly support the antioxidant efficacy of PL, possibly by modulation of antioxidant armory.